2016
DOI: 10.1051/matecconf/20164402012
|View full text |Cite
|
Sign up to set email alerts
|

Guided Waves in a Solid Rod Embedded in Infinite Medium with Weak Interface

Abstract: Abstract. The dispersion relation of the infinite long rod model with a weak interface has been deduced via wave equation of the guided waves and boundary spring interface model. The dispersion characteristics of the rigid interface and the slip interface are calculated, while the effect of different axial stiffness coefficient is also discussed.The results suggest that the phase velocity of the slip interface decreases slowly with increasing frequency at the low frequency of the L (0,1) mode. As for the weak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It is generally known that in layered structures, the thickness of the bonding interface is usually a few micros. Foregoing studies [13][14][15] have revealed that such imperfect interfaces are most simply modeled as spring-type interfaces, where the stresses are continuous, but the displacements suffer discontinuities. These interfaces are hence characterized by their normal and tangential stiffnesses [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally known that in layered structures, the thickness of the bonding interface is usually a few micros. Foregoing studies [13][14][15] have revealed that such imperfect interfaces are most simply modeled as spring-type interfaces, where the stresses are continuous, but the displacements suffer discontinuities. These interfaces are hence characterized by their normal and tangential stiffnesses [16].…”
Section: Introductionmentioning
confidence: 99%